Studies on the use of sodium polyacrylate (SPA) for low-salt animal skin preservation - Balasubramanian, Venkatakrishnan; Velappan, Brindha; Vijayan, Sandhya Kurvilla; Jabamani, Hepzibah; Nagarajan, Vedaraman; Victor, John Sundar; Ranganath, Suresha P.; Badiger, Manohar V.; Chinnaraj, Velappan kandukalpatti; Chellappa, Muralidharan (Environmental Science and Pollution Research, 2019)
Salt-based preservation is practiced for decades in the leather industry because of its versatility, cost-effectiveness, and availability. The salt removed from the soaking process causes significant pollution including organic and elevated total dissolved solids (TDS). Hence, a low-salt skin preservation method using commercial sodium polyacrylate with a reduced quantity of sodium chloride aiming to retain leather properties and pollution reduction was the principal focus of the study. Commercial sodium polyacrylate initially characterized for water absorption capacity along with structural and functional properties is confirmed by NMR and IR spectroscopic techniques. In preliminary experiments, the process parameters attained optimized conditions of sodium polyacrylate (SPA) quantity (5%), a minimal amount of salt (15%), and contact time (4 h) required for skin preservation. Besides, reusability studies after SPA recovery (95%) were applied to skins with an optimized quantity of SPA and salt subsequently stored for 15 days along with control (40% salt). The results revealed that SPA with low salt aided an adequate curing efficiency with a substantial reduction (> 65%) of TDS and comparable physical and organoleptic properties on par with the conventional method. Overall, SPA supported low-salt skin preservation reduces pollutant load (TDS) caused due to using of 40% sodium chloride in the conventional curing process.